Monitoring Mercury (Hg) Pollution at Ambon Bay: the Use of Apogon beauforti as Bioindicator - Dominggus Rumahlatu; Estevanus K. Huliselan (Marine Science Department Diponegoro University, 2016)
Contamination of mercury (Hg) in the sea is one of global issues, including the waters of bay inside the Ambon Island. This research was conducted to monitor heavy metal pollution (Hg) in Ambon bay using Apogon beauforti. This study was conducted by using exploratory survey on physical-chemical environmental factors (temperature, salinity, pH, DO). Hg levels in water, sediments, and A. beuforti were measured, as well as the differences in the morphology of the gills of fish. The sampling technique used in this research was a purposive sampling technique. The environmental factor data were collected in-situ during east and the west season in year 2013 and 2014. The levels of mercury were measured by Atomic Absorbsion Spectrophotometer (AAS). Data were analysed by descriptive statistics. The results showed increasing temperature, salinity and pH within one year (2013-2014) at four different stations. There was a decrease in the levels of Hg concentration in sea water, sediments and A. beauforti at four stations, even though it still remained above the Threshold Limit Value (TLV). The gills of A. beauforti showed dark red, pale and blackish colors indicating the accumulation of heavy metals Hg. Keywords: monitoring, marine pollution, heavy metals Hg, Apogon beauforti, Ambon